Nurses knowledge and practices regarding tracheostomy care at a selected referral hospital in Rwanda - A descriptive cross-sectional study - Tony Gaterega; Marie-Josee Mwiseneza; Geldine Chironda (Elsevier, 2021)
Introduction: Airway Obstruction is a medical emergency that provides an artificial airway support such as the use of endotracheal tubes or creating tracheostomy. To sustain the patency of the airway, a competent nurse is required to deliver care for such kind of patients. Aim: The aim of the study was to assess nurses' knowledge and practices regarding tracheostomy care among patients with tracheostomy tube. Methodology: A quantitative approach, using a cross sectional descriptive study design was used. A convenient sample of 80 nurses working in internal medicine, surgical ward and intensive care units at (RMH) was selected. An adapted structured questionnaire was used to collect data. Descriptive and Inferential statistics were used to analyzed the data. Results: The majority of nurses (71%) had moderate knowledge, 26.5% lower knowledge and Only 2(2,5%) of nurses had high knowledge on tracheostomy definition, types and care. Regarding practice of nurses, a greater number [78(97.5%)] exhibited low levels and only 2(2.5%) with high level of practice regarding the tracheostomy care. There were no significant demographic factors associated with knowledge and practice of nurses. Conclusion: The level of knowledge and practice was limited. Therefore, in-service continuous professional development for registered nurses working in the internal medicine, surgical ward and ICU is highly recommended for further research to elicit the major contributory factors that led to inadequate knowledge and practice.